Basal Cell Carcinoma and Hedgehog Pathway Inhibitors: Focus on Immune Response - Gambini, Donatella; Passoni, Emanuela; Nazzaro, Gianluca; Beltramini, Giada; Tomasello, Gianluca; Ghidini, Michele; Kuhn, Elisabetta; Garrone, Ornella (Frontiers in Medicine, 2022)
Basal cell carcinoma (BCC) is the most common form of skin cancer, affecting more often elderly patients, but sometimes even younger ones, particularly if immunocompromised or genetically predisposed. Specifically, the Gorlin-Goltz syndrome, an autosomal dominant genodermatosis, also known as nevoid basal cell carcinoma syndrome, characterizes for multiple early onset BCCs. It is caused by a germline mutation in PTCH1, a tumor suppressor gene whose product is the key component of Hedgehog (Hh) signaling pathway, which also appears somatically mutated in more than 85% of sporadic BCCs. Hh pathway inhibitors vismodegib and sonidegib are currently indicated for BCC, in adults with advanced or recurred tumor following surgery or radiation therapy. The principal mechanism of action of these drugs is the inhibition of Smoothened (SMO), a transmembrane protein involved in Hh signal transduction, that plays a role in both cellular differentiation and cancer development. Some studies have reported effects of Hh pathway inhibitors at different levels of the immune response, from cytotoxic T cells to a modified local cytokines pattern. Given the specific relation between immune system and BCC development in some conditions, we will review BCC with focus on immune system changes mediated by Hh signaling pathway and induced by the inhibitors vismodegib and sonidegib in the treatment of BCC. Thus, we will give an overview of their effects on the local immune response, as well as a brief note on the supposed function of Hh pathway inhibition on the systemic one.